2018
DOI: 10.1080/10942912.2018.1425702
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, purification, and antioxidant activities of polysaccharides from Ziziphus Jujuba cv. Muzao

Abstract: In the present study, crude polysaccharides from Ziziphus Jujuba cv. Muzao were isolated and purified using DEAE cellulose-52 and Sephadex G-100 size-exclusion chromatography; four fractions were collected, namely GZMP-1, GZMP-2, GZMP-3, and GZMP-4. The molecular weights of these four fractions were measured to be 111.2, 95.1, 84.2, and 571.4 kDa, respectively, using high-performance gel permeation chromatography. Gas chromatography analysis of the monosaccharide composition confirmed that GZMP-1 was composed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 38 publications
(49 reference statements)
1
5
0
Order By: Relevance
“…Due to the direct relationship between phenolic compounds and antioxidant activity, high content of phenolic compounds could be expected. This extract had a high inhibitory effect and these findings are in agreement with those obtained by other researchers ( Choi et al, 2012 ; Gao, Wu, Wang, Xu, & Du, 2012 ; Yu et al, 2012 ; Wang et al, 2016 ; Ji, X, Liu, Ullah, & Wang, 2018 ). It can obviously be resulted that the use of this fruit as a source of bioactive compounds and natural antioxidants is effective in promoting the quality and development of functional foods and nutraceuticals.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Due to the direct relationship between phenolic compounds and antioxidant activity, high content of phenolic compounds could be expected. This extract had a high inhibitory effect and these findings are in agreement with those obtained by other researchers ( Choi et al, 2012 ; Gao, Wu, Wang, Xu, & Du, 2012 ; Yu et al, 2012 ; Wang et al, 2016 ; Ji, X, Liu, Ullah, & Wang, 2018 ). It can obviously be resulted that the use of this fruit as a source of bioactive compounds and natural antioxidants is effective in promoting the quality and development of functional foods and nutraceuticals.…”
Section: Resultssupporting
confidence: 93%
“…As tabulated in Table 5 , total phenol content of jujube extract during the storage time decreased by approximately one-third on the 14th day. The adverse effect of environmental parameters on these compounds such as ambient light, oxygen in the head space of the extract storage medium and storage time on the reduction of some phenolic compounds has been reported by several authors ( Gao, Wu, Wang et al, 2012 ; Ji et al, 2018 ; Wang et al, 2016 ). Some researchers extracted phenolic compounds using different solvents ( Mokrani and Madani, 2016 ).…”
Section: Resultsmentioning
confidence: 94%
“…It is well-known that the specific functional groups, e.g., sulfate, amino, hydroxyl, and carboxyl ones, can be related to the antioxidative effect of polysaccharides [ 36 ]. It was found that all the HC samples have the lower activity with respect to DPPH as compared with Vc.…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that HC Mn exhibited the strongest scavenging activity, but HC H2SO4 had the weakest scavenging activity over the entire range of 0.08–2.0 mg/mL. This is due to the fact that the contents of carboxyl and methoxyl groups of uronic acids, as well as the high content of hydroxyl groups positively affect the antioxidant activity of polysaccharides [ 36 , 37 , 38 ]. In addition, it was reported [ 39 ] that the galactose-rich polysaccharides have a relatively high antioxidant activity, which is consistent with our data on the monosaccharide composition.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown in many studies [ 4 , 32 , 46 ] that plant polysaccharides are able to scavenge free radicals and can be used as natural antioxidants. To determine the ability of antioxidants to scavenge free radicals, DPPH is commonly used, showing the strong absorption at 517 nm [ 4 ].…”
Section: Resultsmentioning
confidence: 99%